Implementasi Total Quality Management (Manajemen Mutu Terpadu) di SDI Sabilina Bekasi - Nurhadi Kastamin; Maemunah Sa’diyah; Nur Afif (Reslaj : Religion Education Social Laa Roiba Journal, 2021)
The purpose of this study is to describe how the implementation of Total Quality Management (TQM) at SDI Sabilina, Cibur, Bekasi. In this study, the author uses descriptive qualitative methods, namely research methods that utilize qualitative data and are described descriptively. Data was collected using in-depth interviews, observation, and documentation methods. The research was conducted on Wednesday, June 09, 2021, at SDI Sabilina from 13.00-16.00. Checking the validity of the data is carried out through member checks, namely the process of checking data carried out by researchers to research subjects or resource persons, and discussions with colleagues.